Dangerous Extracranial–Intracranial Anastomoses: What the Interventionalist Must Know - Rinaldo, Lorenzo (Semin Intervent Radiol, 2020)
The extracranial and intracranial circulations are richly interconnected at numerous locations, a functional connectivity which underlies their impressive capacity for adaptive plasticity in the setting of vasoocclusive disease. While evolutionarily beneficial, these connections can also result in inadvertent communication with the intracranial circulation during embolization of extracranial vessels, potentially resulting in stroke or cranial nerve palsy. While these anastomoses are always present to a certain extent, flow through them occurs under predictable circumstances, and thus embolization of the extracranial vasculature can be performed safely when knowledge of functional anatomy is combined with adherence to basic principles. Herein, we will review the anatomy of known extracranial–intracranial anastomoses and strategies for avoidance of unwanted intracranial embolization. We will also review the vascular supply to cranial nerves most at risk during common neurointerventional procedures, as well as blood supply to mucosal structures.